A+BX=CX+D

Simple and best practice solution for A+BX=CX+D equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A+BX=CX+D equation:


Simplifying
A + BX = CX + D

Solving
A + BX = CX + D

Solving for variable 'A'.

Move all terms containing A to the left, all other terms to the right.

Add '-1BX' to each side of the equation.
A + BX + -1BX = CX + -1BX + D

Combine like terms: BX + -1BX = 0
A + 0 = CX + -1BX + D
A = CX + -1BX + D

Reorder the terms:
A = -1BX + CX + D

Simplifying
A = -1BX + CX + D

See similar equations:

| 4(Z+7)-6=2 | | 29-(-q)=86 | | xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= | | I=IR | | 5x+5x+130=180 | | -12+5m+10m=-2m-10-m | | 4(3x+3)=14x+11-2x+1 | | (3a-5)(2a+3)=0 |

Equations solver categories